KITOSAN TERMODIFIKASI TRIPOLIFOSFAT SEBAGAI KANDIDAT MATERIAL PELAPIS ARTEFAK KAYU - Tri Windarti; Fenina Azalia Dewi Hascaryo (Balai Konservasi Borobudur Magelang, 2022)
Chitosan is one of natural polymers that has been widely developed for the conservation of wood artifacts. Chitosan modification with tripolyphosphate (TPP) crosslinker aims to change the linear structure of chitosan into networking. This structural change is expected to improve the performance of chitosan coating on the surface of wood artifacts. The aims of this research are to study the effect of NaTPP concentration (0.5 – 10%) as a source of TPP and sonication time (5 – 25 minutes) on the structure and morphology of chitosan. The results showed that identification of phosphate content by using UV-Vis spectrometer confirmed that no phosphate ion found in the remaining reaction solution. Treatment with sonication caused all TPP ions to physically interact with chitosan. FTIR spectra are difficult to confirm the presence of TPP because of the overlap between the energy of the phosphate vibration and the C-O stretching vibration of chitosan. TPP modified chitosan is in the form of a thin and transparent film. SEM images show that the surface of the chitosan is flat, dense and non-porous. The results of the elemental composition test with EDX showed the presence of carbon (64.98%), nitrogen (0.2%), oxygen (34.69%), and phosphorus (0.01%) on the chitosan surface. Thus, TPP-modified chitosan can be used as a candidate for wood artifact coating material, to avoid the infiltration of water molecules in the air without changing the original appearance of the artifact.